2000
DOI: 10.1039/a907765k
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic and lyotropic behavior of novel amphiphilic liquid crystals having hydrophilic poly(ethyleneimine) units

Abstract: Novel ionic amphotropic liquid crystals, in which a hydrophilic poly(ethyleneimine) chain with hydroxy side-groups was attached to an azobenzene mesogenic core through an alkylene chain, showed a thermotropic smectic A mesophase and lyotropic smectic A and C mesophases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…Our group also reported that PEI having nitro substituent azobenzene side chain group showed out-of-plane molecular orientation on a glass substrate by annealing but not upon non-polarized visible light irradiation [8]. In addition, Ujiie group reported that some polyethylene imines (PEIs) having azobenzene groups as side groups show liquid crystalline phases and align perpendicular direction to the substrate spontaneously by heating and following cooling without any alignment process [9,10]. So, by photochemically controlling the molecular orientation of PEIs between random state and out-of-plane structures, one can fabricate the optical switching system showing excellent memory stability by coating PEIs on a substrate without any alignment process.…”
Section: Introductionmentioning
confidence: 87%
“…Our group also reported that PEI having nitro substituent azobenzene side chain group showed out-of-plane molecular orientation on a glass substrate by annealing but not upon non-polarized visible light irradiation [8]. In addition, Ujiie group reported that some polyethylene imines (PEIs) having azobenzene groups as side groups show liquid crystalline phases and align perpendicular direction to the substrate spontaneously by heating and following cooling without any alignment process [9,10]. So, by photochemically controlling the molecular orientation of PEIs between random state and out-of-plane structures, one can fabricate the optical switching system showing excellent memory stability by coating PEIs on a substrate without any alignment process.…”
Section: Introductionmentioning
confidence: 87%
“…We also reported that PEI having nitro substituent azobenzene side chain group showed out-ofplane molecular orientation on a glass substrate by annealing but not upon non-polarized visible light irradiation 12 . In addition, Ujiie group 13,14 reported that some polyethene imines (PEIs) having azobenzene as side groups show liquid crystalline phases and align perpendicular to the substrate spontaneously by heating and followed by cooling without any alignment process. So, by photochemically controlling the molecular orientation of PEIs between random state and out-of-plane structures, one can fabricate the optical switching system showing excellent memory stability by coating PEIs on a substrate without any alignment process.…”
Section: Introductionmentioning
confidence: 99%
“…Amphiphilic compounds can form a variety of thermotropic liquid-crystalline phases as a function of temperature by themselves, and lyotropic liquid-crystalline phases upon addition of some solvent, such as water or diethylene glycol [1]. Thermotropic liquid-crystalline systems composed of amphiphilic molecules can exhibit smectic phases with layered structure [2] or nematic (eventually cholesteric) phases. Lyotropic systems usually form a lamellar liquid-crystalline mesophase, i.e., a lyotropic analogue of the thermotropic orthogonal smectic A (SmA) phase [3], and more rarely nematic, columnar and cubic mesophases [45].…”
Section: Introductionmentioning
confidence: 99%
“…The thermotropic SmA phase and hexatic/cubic/lamellar lyotropic phases have been detected for a series of 4-alkoxyphenyl β-D-glucopyranosides [5]. LC compounds in which a hydrophilic polyethyleneimine chain with hydroxy side-groups is attached to the azobenzene mesogenic core through the alkylene chain have showed a thermotropic SmA phase, lyotropic lamellar phase, and a lyotropic analogue of the tilted smectic C phase [2]. Due to microsegregation of the hydrophilic regions from aromatic segments in the absence of flexible alkyl chains, the thermotropic and lyotropic smectic and columnar phases have been detected for 4-benzyloxy-4’-(2,3-dihydroxypropyloxy)biphenyls with lateral methyl substituents [19].…”
Section: Introductionmentioning
confidence: 99%